PENILAIAN RISIKO PENGENAAN SANKSI ADMINISTRATIF PERPAJAKAN ATAS PELAPORAN PAJAK (Studi Kasus pada PT "X" Bandung) - Lusy Suprajadi; Elvy Maria Manurung; Sylvia Kumala Dewi C. (Bina Ekonomi, 2011)
Tax reporting which is made based on good and prudent company finance report is getting more  important  to know and make by companies. This is according  to the tax regulation still  in effect.  This  is due  to the system for collecting  tax applied  in Indonesia  that  is self assessment.   The system  gives the people authorization, trust, and responsibilities  to the  tax payer  to count,  pay, and report by themselves. The system gives  them a kind of space  to fulfill their  tax obligation. Design and implementation of the system and procedure  of tax reporting-by  companies-will determine the quantity and obedience of companies  in reporting  their  tax obligation. The system and procedure  are by themselves a system  for measuring the rate of risk of being penalized  based on their  finance  report.  The paper will analyze  the research  result in the design and  implementation  of the system and tax reporting  procedure  PT “X" in a company in Bandung.  The methodology applied is descriptive evaluative, that is to examine  the company current condition  through  observations,  interviews, and documentations  study.  The  result shows that the company  still makes some mistakes  in reporting its  tax from which it receives consequence of being given  tax penalty.  It is recommended  that  the company  starts to improve its  system and procedure of tax reporting in order that  tax penalty be reduced  to the minimum and also  increase  the quality of its tax reporting.